Biomembrane-coated multifunctional “core-shell” nanoparticles for magnetic hyperthermia induced immunotherapy - Junnan Kan; Jin Tao; Junhui Wei; Haiyan Gao; Yijie Lv; Mingfang Luo; Kai Qi; Hengyi Qin; Tingting Wang; Caixia Yang; Xianglin Li (Materials & Design)
Breast cancer is still one of the main threats to women’s health and the development of versatile nanotheranostic agents is of importance. Herein, multifunctional “core–shell” nanoparticles were described by decorating the MnO2 shell on the Fe3O4 core and further coated with 4T1 cancer cell membrane (FMC). The FMC showed multi-modal imaging ability with switchable magnetic resonance imaging (MRI) from T2 to T1/T2 and photoacoustic imaging (PAI) in the tumor microenvironment due to the dissolution of the MnO2 shell. Moreover, the cancer cell membrane coating could effectively promote the cancer cell uptake through homotypic targeting. FMC nanoparticles accumulated in the tumor areas were heated under an external alternating magnetic field, driving a magnetic hyperthermia-induced anti-tumor immune response. Our in vitro and in vivo studies showed that self-targeting FMC efficiently localized in 4T1 cancer cells and realized efficient magnetic hyperthermia/immunotherapy with the imaging assistance of T1/T2 MRI and PAI.